Nurses’ knowledge on pharmaceutical care with their perception & expectation on the potential roles of pharmacist in private outpatient haemodialysis centres - Mahdzir, Zulhasri; Mohamed Nazar, Nor Ilyani; Mohamad Noor, Zaswiza (2019)
INTRODUCTION Pharmaceutical care issues are common among ambulatory haemodialysis patients. Provision of pharmaceutical care by pharmacist has benefitted this population but it is yet to be implemented in private haemodialysis centre. OBJECTIVES To develop and validate a questionnaire which later on is used to evaluate nurses’ knowledge on pharmaceutical care aspects of patient care; and to assess nurses’ perception, expectation, and willingness on potential roles of pharmacist in private haemodialysis centre. METHOD A set of questionnaire was developed after extensive literature review of related studies. Content validity index was used to examine the validity of questionnaire. Cronbach’s alpha was computed for reliability study. A descriptive, cross-sectional study was conducted among nurses in private haemodialysis centres in Kuantan, Pahang using the questionnaire. Data was entered into SPSS IBM version 21, where descriptive and inferential analyses were conducted. RESULTS Scale-level content validity index calculated was 0.91. Cronbach’s alpha generated reached 0.70. A total of 63 nurses participated in this study. More than half of them (52.4%) demonstrated adequate knowledge regarding pharmaceutical care aspect of patient care. Majority of them (84.1%) agreed that pharmacist is reliable as the source for general and clinical drug information. About 50.8% of them expected pharmacist to resolve any pharmaceutical care issues encountered. A large proportion of them (76.2%) were willing to work with the pharmacist in private haemodialysis centre. CONCLUSION Over half of those surveyed had positive perception and high expectation on the potential roles of pharmacist which can have positive outcomes for future implementation of pharmaceutical care services in private haemodialysis centre.